2015
DOI: 10.1016/j.jaci.2015.04.039
|View full text |Cite
|
Sign up to set email alerts
|

CTNNA3 and SEMA3D: Promising loci for asthma exacerbation identified through multiple genome-wide association studies

Abstract: BACKGROUND Asthma exacerbations are a major cause of morbidity and medical cost. OBJECTIVE The objective of this study was to identify genetic predictors of exacerbations in subjects with asthma. METHODS We performed GWAS meta analysis of acute asthma exacerbation in two pediatric clinical trials: Childhood Asthma Management Program (CAMP, n=581) and Childhood Asthma Research and Education (CARE, n=205) network trials. Acute asthma exacerbations was defined as treatment with a five-day course of oral stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 51 publications
(60 reference statements)
3
43
0
1
Order By: Relevance
“…Our findings mechanistically support several human GWA studies linking αT-cat ( CTNNA3 ) to steroid-resistant asthma in children(3) asthmatic exacerbations in children(4), and occupational asthma in adults (13, 14). Importantly, we found that loss of αT-cat is associated with a dramatic reduction in PV inflammation in the HDM murine model of atopic asthma, suggesting that cardiomyocytes within PV may contribute to the inflammatory milieu of adjacent airways.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Our findings mechanistically support several human GWA studies linking αT-cat ( CTNNA3 ) to steroid-resistant asthma in children(3) asthmatic exacerbations in children(4), and occupational asthma in adults (13, 14). Importantly, we found that loss of αT-cat is associated with a dramatic reduction in PV inflammation in the HDM murine model of atopic asthma, suggesting that cardiomyocytes within PV may contribute to the inflammatory milieu of adjacent airways.…”
Section: Discussionsupporting
confidence: 87%
“…Remarkably, the most recent human genomic data identifying polymorphisms associated with asthma exacerbations in children(4) further support the notion of a cardiac cell/PV contribution to asthma, with αT-cat ( CTNNA3 ) as the top-hit and two other associated genes with direct and established cardiac cell/PV functions(4). These included the sarcomere structural protein, titin, which is important for the contraction of cardiac tissues(24) and the secreted vascular guidance protein, semaphorin 3d, whose primary role is in patterning and development of the PV(25).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations